2018
DOI: 10.1177/1060028018819450
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Assessment of Drug-Induced Thrombocytosis

Abstract: Objectives: The purpose of this article is to review the current literature on drug-induced thrombocytosis with the goal of critically assessing causality and providing a comprehensive review of the topic. Thrombopoietic growth factors, such as thrombopoietin-receptor agonists (romiplostim and eltrombopag) and erythropoietin are not included in our review. Data Sources: The literature search included published articles limited to the English language and humans in MEDLINE, EMBASE, and Web of Science databases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
(139 reference statements)
0
16
0
1
Order By: Relevance
“…In addition to the subcutaneous injections of enoxaparin, the patient was given oral medications including amlodipine, telmisartan, aspirin, and atorvastatin. Previous research have revealed that some medications including All-Trans Retinoic Acid (ATRA), Antibiotics, Clozapine, Epinephrine, Gemcitabine, Low-Molecular-Weight Heparins (LMWHs), and Vinca Alkaloids may lead to drug-induced thrombocytosis, and the strongest evidence of causality supports LMWH and neonatal drug withdrawal as the main etiologic factors [6]. Based on this facts, we suspected that the patient's thrombocytosis was induced by enoxaparin, so anticoagulation with rivaroxaban instead was initiated on the 16th day of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the subcutaneous injections of enoxaparin, the patient was given oral medications including amlodipine, telmisartan, aspirin, and atorvastatin. Previous research have revealed that some medications including All-Trans Retinoic Acid (ATRA), Antibiotics, Clozapine, Epinephrine, Gemcitabine, Low-Molecular-Weight Heparins (LMWHs), and Vinca Alkaloids may lead to drug-induced thrombocytosis, and the strongest evidence of causality supports LMWH and neonatal drug withdrawal as the main etiologic factors [6]. Based on this facts, we suspected that the patient's thrombocytosis was induced by enoxaparin, so anticoagulation with rivaroxaban instead was initiated on the 16th day of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced thrombocytopenia is considered one of the causes of secondary or reactive thrombocytosis [ 7 ]. Many drugs were reported previously to cause thrombocytosis e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Many drugs were reported previously to cause thrombocytosis e.g. penicillins, cephalosporins, clozapine, and others [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Гемостаз являє собою фізіологічний процес своєрідного балансування між процесами підтримки рідкого стану крові та тромбоутворення. Ця система є складною, динамічною компонентою, яка складається з пов'язаних між собою плазмових факторів та клітин -тромбоцитів [14,17].…”
unclassified